2018
DOI: 10.14197/atr.201218115
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Overlapping Migratory Categories within New Patterns of Mobility in Peru

Abstract: This article reflects on the construction and application of different migratory categories in the Peruvian context, including irregular migrants, refugees, victims of trafficking, and smuggled migrants. Through legal analysis and interviews with key migration actors in the country, the paper explores the ways in which Peru responds to migrants in these different categories, in view of the recent changes in human mobility in the country. The article aims to shed light on the fragmentation of migratory categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…22 Moreover, the office of Peru's Attorney General has published a protocol about how to identify, rescue and attend to victims of human trafficking, with a special focus on underage victims. 23 However, it has been pointed out that the overlap in the mandates, and a lack of coordination between institutions responsible for attending trafficking victims, render their protection difficult in practice (Blouin & Button, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Moreover, the office of Peru's Attorney General has published a protocol about how to identify, rescue and attend to victims of human trafficking, with a special focus on underage victims. 23 However, it has been pointed out that the overlap in the mandates, and a lack of coordination between institutions responsible for attending trafficking victims, render their protection difficult in practice (Blouin & Button, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding transnational trafficking to Peru, authors have lamented the scant literature and data available (Blouin, 2017). As noted by Blouin and Button (2018), Peru is challenged with identifying and protecting victims of human trafficking -both foreign and national. While Peru is a "country considered as the place of origin, transit and destination of international trafficking", internal trafficking is predominant and linked to sexual and labor exploitation in mining, logging, agriculture and domestic work (Cortés Toro, 2007, p. 86).…”
Section: Human Trafficking and Domestic Labor In Perumentioning
confidence: 99%
“…Research has shown that for the populations who are the subject of migration policy, their experience does not always fall into such discrete and mutually exclusive categories. For example, studies have shown that terms presented as mutually exclusive can be used to describe the same groups and have shown boundaries are blurred between the categories of 'smuggled migrants' and 'asylum seekers' or 'trafficked persons' and 'irregular migrants' (Blouin andButton, 2018), and'refugees' and'trafficking victims' (Anderson andLi, 2018), and 'victims of trafficking', 'smuggled migrant', 'illegal alien', and 'refugee' (Soltis and Walters, 2018). The unreliable nature of these categories is concerning as the way a person is categorised determines their legal status and the services available to them.…”
Section: Using Narrative Criminology To Analyse Human Trafficking As ...mentioning
confidence: 99%
“…These definitions have been critiqued as misrepresentations and as not capturing the reality for women who chose to travel and work in the sex industry and who express agency and consent in doing so (for example : Cojocaru, 2016;Hoefinger, 2016;Tomkinson, 2012;Mahdavi and Sargent, 2011;Lebov, 2010;Andrijasevic, 2007;GAATW, 2007;. Other literature has criticised top-down definitions and responses to trafficking as presenting oversimplified characterisations of migrants, victims and offenders which do not capture the complex realities of people moving for work (for example: Anderson and Li, 2018;Blouin and Button, 2018;Juliawan, 2018;Sanchez, 2018;Soltis and Walters, 2018;Mahdavi and Sargent, 2011).…”
Section: Differing Narratives At International and New Zealand Levelmentioning
confidence: 99%
See 1 more Smart Citation